2015
DOI: 10.3944/aott.2015.15.0016
|View full text |Cite
|
Sign up to set email alerts
|

Is there any clinical superiority of the anteromedial portal compared to the Transtibial in Anterior Cruciate Ligament reconstruction in non-professional athlete patients in short term follow-ups?

Abstract: The AM technique has no clinical superiority compared to the TT technique in ACL reconstruction in nonprofessional athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Several studies have shown that the AM elicited greater knee stability and improved the functional outcomes [ 17 , 18 , 23 , 24 ]. On the contrary, other researchers have claimed that no definitive evidence could conclude that the AM technique was superior to the TT technique [ 10 , 25 – 29 ] and the former might increase several other complications [ 17 , 30 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the AM elicited greater knee stability and improved the functional outcomes [ 17 , 18 , 23 , 24 ]. On the contrary, other researchers have claimed that no definitive evidence could conclude that the AM technique was superior to the TT technique [ 10 , 25 – 29 ] and the former might increase several other complications [ 17 , 30 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two important ligaments providing this stability are the anterior cruciate ligament (ACL) and the posterior cruciate ligament (PCL), the anatomy of which are becoming increasingly known [14]. As a result of studies which have focused on the equivalence of the ACL and PCL projections, there has been extensive research on the anatomic dimensions of the ACL and PCL and variations have been determined in various individuals [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ilahi et al 1 reported a mean femoral tunnel clock-face position of 10:18 (range, 10:00-10:30) in patients treated with the AAMP technique. Taşdemir et al 28 reported a mean femoral tunnel clock-face position of 10:10 (range, 9:50-10:25) in patients treated with the AMP technique. In this study, the mean femoral tunnel clock-face position was 10:13 (range, 09:42-10:33) in the AMP group and 10:24 (range, 9:49-10:46) in the AAMP group for the right knee; for the left knee, these values were 1:49 (range, 1:33-2:03) in the AMP group and 1:36 (range, 1:23-1:45) in the AAMP group.…”
Section: Discussionmentioning
confidence: 99%
“…The independent AMP technique is thought to achieve better positioning of the femoral tunnel and the native ACL footprint and allow more posterior positioning of the graft on the wall of the lateral femoral condyle than the traditional TT approach. 27,28 A recent cadaveric study demonstrated that the AAMP technique provided greater accuracy than the TT technique in creating anatomical femoral tunnels. 1, 20 The AAMP technique is an alternative to the above-mentioned techniques and offers the following advantages.…”
mentioning
confidence: 99%